2003
DOI: 10.1089/154545703322460621
|View full text |Cite
|
Sign up to set email alerts
|

Bovine and Ovine Blood Mononuclear Leukocytes Differ Markedly in Innate Immune Responses Induced by Class A and Class B CpG-Oligodeoxynucleotide

Abstract: Cytosine-phosphate-guanosine (CpG)-DNA can induce an impressive array of innate immune responses that may directly or indirectly contribute to the clearance of infectious agents. Assays, such as lymphocyte proliferative responses, have been used to demonstrate that the immunostimulatory activity of CpG-DNA is conserved among a broad range of vertebrate species, but no studies have been completed to determine if qualitative differences exist among species for CpG-oligodeoxynucleotide (ODN)-induced innate immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…ODN 2216 was a strong immunoregulator for activating pDCs and inducing high amounts of IFN-␣ [30,41,42]. We found that the ODN 2216 itself could not inhibit HBV replication directly.…”
Section: Discussionmentioning
confidence: 83%
“…ODN 2216 was a strong immunoregulator for activating pDCs and inducing high amounts of IFN-␣ [30,41,42]. We found that the ODN 2216 itself could not inhibit HBV replication directly.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, both ODN 2216 and ODN 2007 induced CpG-specific non-MHC-restricted cytotoxicity with ovine but not bovine PBMC. Even more interestingly, in these studies there was not a single assay in which PBMC from all sheep or cattle responded at a detectable level [49]. A striking aspect of these results is that such marked differences in CpG-ODN-induced innate responses existed both between and within two closely related species.…”
Section: Endosomal Tlrsmentioning
confidence: 89%
“…Subsequent analyses confirmed that the GTCGTT motif, which has optimal activity in humans, is also active in various domestic species, whereas the GACGTT motif, displaying the greatest activity in the murine system, showed little or no activity in any of these domestic species. Furthermore, TLR9 from different species recognizes a species-specific optimal CpG ODN [49]. Within ruminants, for example, ODN 2007 only works in the ovine system, whereas ODN 2216 only stimulates bovine peripheral blood monocytes (PBMC).…”
Section: Endosomal Tlrsmentioning
confidence: 99%
“…Distinct responses to CpG-ODN have been described in different species. Mena et al [59] have shown a specific and dose-dependent IFNα response to class B CpG-ODN motif-stimulated ovine, but not bovine, peripheral blood mononuclear cells. In addition, class B CpG-ODN has been shown to induce in vitro IFNα production in newborn lambs, which seems to contrast with our findings in foals [60].…”
Section: Discussionmentioning
confidence: 99%